Synthesis and characterization of gel-type polymers via aqueous dispersion polymerization - Nur Atiqah , Mohamad (2015)
This study is about synthesis and characterization of gel-type polymer aqueous dispersion polymerization (ADP) that involved two types of dispersion polymerization methodology; one-stage aqueous dispersion polymerization and two-stage aqueous dispersion polymerization. The monomer and crosslinker were used in this study are styrene and EGDMA. Mixture of styrene and solvent undergone under nitrogen atmosphere for one hour at 70 °C before EGDMA was added into the mixture. The reaction was continued further 23 hours before the final product obtained. The polymers are characterized by using FTIR and CHNOS analysis. For one-stage polymerization, the final product was successfully obtained after 24 hours of reaction. The result obtained was not in bead-like shape but in flakes-formed. For two-stage ADP, based on the result from FTIR for two-stage polymerization, it shows that there are functional group that has been identified; alkene and alcohol and phenols reflect to functional group in styrene and EGDMA. It is clearly shown that EGDMA and styrene are incorporated in the back bone of polymer. For elemental analysis, CHNOS shows that there are 6.97% of nitrogen, 88.56% of carbon, 7.66% of hydrogen and 0.01% of sulphur at temperature of 70 oC while at 72 oC is 93.73% of nitrogen, 82.07% of carbon, 6.67% of hydrogen and 0.23% of sulphur. In conclusion, the particles were obtained in broad particles size distribution and polydisperse by varying the temperature for the reaction in two-stage ADP.